Perception of health and illness and quality of life after total thyroidectomy for differentiated thyroid carcinoma: the PERSAM study - Groff, Elena; Soccal, Beatrice; Carrossa, Fabiola; Vianello, Federica; Talomo, Sara; Feltrin, Alessandra; Scarzello, Giovanni; Ocagli, Honoria; Gregori, Dario; Martinato, Matteo (Frontiers in Endocrinology, 2024)
BackgroundDifferentiated thyroid carcinoma is the most common endocrine neoplasm; several studies have shown that individuals perceive the disease as being more severe than it actually is, resulting in a reduced quality of life. The primary aim of this study is to assess the quality of life and perception of illness among patients admitted for radiometabolic therapy, post total thyroidectomy for differentiated thyroid carcinoma. The secondary aim is to identify which patient characteristics are associated with a lower quality of life in order to improve and personalize care.MethodsThe study was conducted at the UOC of Radiotherapy Veneto Institute of Oncology IOV-IRCCS in Padua, Italy. Three questionnaires were administered: Psychological General Well-Being Index (PGWBI), the Illness Perception Questionnaire (IPQ-R) and the Short Form Survey (SF-12). A descriptive statistics analysis and multiple linear regression models were performed to explore the relationship between some of the variables.ResultsSignificant associations emerged between the type of surgery and higher values on the PGWBI questionnaire (P = 0.022) and the score obtained in the ‘emotional representations’ dimension of the IPQ-R questionnaire (P = 0.028). Pathology staging was statistically significantly (P = 0.026) associated with the score obtained in the dimension ‘identity’; age with the scores obtained in the dimensions ‘emotional representations’ (P = 0.035), ‘personal control’ (P = 0.004), ‘consistency with pathology’ (P < 0.001) and ‘causes’ (P = 0.004).ConclusionsThere is evidence of moderate distress in psychological well-being and good perception of pathology. There is less understanding of the disease in individuals with stage 3 and 4 thyroid cancer, in those who have undergone total thyroidectomy without lymphadenectomy and who are aged over 60. Physical well-being: limitations in self-care and moderately physically demanding activities. Mental health: more information to patients decreases the degree of stress and promotes ‘positive’ emotions. Physical health status: a long-term activity program, characterized by aerobic exercises to be performed in groups or at home, is useful. This study allows to transpose the results into clinical practice, evaluating the possibility and methods of providing personalized care to patients.